بائبل اور سیرت طیبہ کی روشنی میں نسوانی معاشی کردار کا تقابلی وتجزیاتی مطالعہ: The Economic Role of Women in the light of the Bible and Prophetic Sīrāh: An Analytical and Comparative Study - Dr. Tehseen Sarwar; Muhammad Qasim (MEI, 2023)
Islam is a religion that examines everything on the basis of fitrah standards. From ancient times to the present, different views have been debated regarding the economic role of women in the Bible and Prophet’s (ﷺ) Sīrāh. However, in Christian scholarship and Islamic teachings, the overall roles of women have been discussed separately in different contexts. The present article seeks to highlight the economic role of women in the Christian era and the Prophet’s (ﷺ) regime to present their status in both societies. According to today’s difficult and unfavorable economic situation, it is imperative that the Christian and Prophetic (ﷺ) eras be exemplified for awareness and guidance. The research covers various occupations of women such as breastfeeding, care, cooking, driving, industry, craft, farming, teaching, business and inheritance. The terms of business have also been clarified. Moreover, the analytical and comparative methodology is adopted to examine the Biblical text and the Prophetic (ﷺ) Sīrāh. In short, the research seeks to bridge the gap between Muslim and Christian communities by removing misconceptions about the economic role of women.